Premium, pertalite or pertamax: an empirical study of Alchian-Allen phenomenon on gasoline consumer behavior - Nur Laila Widyastuti; Djoni Hartono (Universitas Hayam Wuruk Perbanas, 2019)
In Indonesia, consumers can choose to consume either high or low quality gasoline based on their preferences. Changing preference to a higher quality that is affected by the declining relative price can lead to an Alchian-Allen (A-A) phenomenon. This study aims to determine whether the A-A Phenomenon occurs on the behavior of consumers before and after the existence of Pertalite. The regression model used is the panel data regressions and the regression result proves that there is an A-A phenomenon in market share in Indonesia before and after Pertalite. This indicates that the high difference of relative prices between high and low quality gasolines has a negative impact towards their relative consumption. Prior to Pertalite, consumers continued changing preference into high quality gasoline in the 2nd and 3rd month intervals when relative price difference decreased. After the existing of Pertalite, consumers did not quickly transfer their preferences from Premium to Pertalite when the relative price declined, so that the A-A phenomenon did not occur in this low and middle grade gasoline consumption pattern. However, Pertamax's consumption to Pertalite increases when the relative price between them declines; thus raising the A-A phenomenon. This implies that the government of Indonesia could use their authority to make arrangements on price differences between gasoline qualities